"I think I sound stupid if I try to use those words": The role of metapragmatic awareness in the study abroad language classroom. (10th May 2018) - Fernández, Julieta
Abstract: This study investigates the instructional treatment of Argentine Spanish vernacular (i.e., lunfardo ), metapragmatic information about its use provided by instructors, and participants' metapragmatic awareness of vernacular use in a second language (L2) Spanish study abroad (SA) classroom. The participants were 12 American undergraduate students taking Spanish courses at an SA institute in Argentina. The educators were eight university‐level instructors who were native speakers of Argentine Spanish. The analysis triangulates data from classroom observations, classroom materials, a language awareness test, and semi‐structured interviews with the participants. The results indicate that although the L2 instructors provided instruction on the use of vernacular, they appeared to do so without providing sufficient metapragmatic information for the students to understand and use vernacular competently in interactions with locals. The significance of a pedagogical focus on vernacular that begins predeparture and encourages active student participation is discussed. The Challenge: The teaching of vernacular expressions (including slang and taboo) in the foreign language classroom is a source of controversy. What aspects of vernacular can or should educators address in the language classroom? How should they go about teaching vernacular?